The relationship between platelet glycoprotein VI T13254C polymorphism and acute myocardial infarction (MI) - A Fatemi; A Kazemi; MM Peighambari; N Givtaj; H Bakhshandeh (Tehran University of Medical Sciences, 2011)
Background and Aim: Myocardial infarction (MI) is a major cause of morbidity and mortality worldwide. Epidemiological studies indicate that MI results from complex interactions between long-term environmental influences, concomitant disorders, and genetic susceptibility factors. Identification of genetic risk factors, particularly in premature MI, is very important. Since thrombosis plays a critical role in the pathophysiology of MI, recent studies focus on coagulation genetic polymorphisms. The critical role of platelets and their surface glycoproteins in the formation of occlusive thrombus leading to acute myocardial infarction is now well accepted. Platelets have two major receptors for collagen, glycoprotein I/IIa (integrin α2β1) and glycoprotein VI. In the present study, platelet GP VI T13254C polymorphism was chosen due to its potential association with altered platelet reactivity. The aim of the present study was to determine whether or not GP VI T13254C polymorphism was associated with premature acute myocardial infarction. Materials and Methods: One hundred patients with premature acute myocardial infarction and 100 age-matched controls with normal coronary angiograms were studied. Genotyping was done using PCR followed by RFLP. Statistical analyses included chi-square, t-test and logistic regression model. Results: The findings of the present study showed that the prevalence of T13254C polymorphism did not differ much between patient (38%) and control (33%) groups and that polymorphism was not associated with premature acute MI (P=0.46). Logistic regression analysis also indicated no association between this polymorphism and premature acute MI (P=0.20). Conclusion: This study showed that there was no significant association between GP VI T13254C polymorphism and premature acute MI.